Retrospective denoising and sharpening effects on postmortem computed tomography images of formalin-fixed human cadavers for human anatomy education and research - Tomokazu Kawashima; Norihiro Sudou; Makoto Sakai; Fumi Sato (Elsevier, 2024)
Background: The value of formalin-fixed postmortem computed tomography (PMCT) has significantly increased in human anatomy education and research. However, improving embalmed PMCT images with high noise, low contrast, and multiple artifacts is an important challenge in enhancing the quality of clinical images. Retrospective denoising methods for embalmed PMCT data are essential for anatomical education and research when new-generation CT scanners with denoising functions are unavailable. Methods: The three currently available standalone software denoising methods, including image summation methods (Fused CT), noise-reduction system methods (iNoir), and iterative reconstruction (IR, SafeCT), were used to analyze the retrospective noise-reduction effect on 13 human formalin-fixed PMCT datasets. Results: Fused CT had some advantages; however, it was not useful for embalmed cadavers because of high noise, which doubled with the addition. iNoir and SafeCT improved the visual image quality of the noisy cadaver images. Statistical examination showed a 22-67 % and 18-56 % improvement in noise reduction in the non-artifact and metal artifact parts, respectively, depending on the methods and denoising intensities. However, this improvement was not statistically or morphologically significant in the presence of strong metal artifacts. In contrast, the scattered metal and streak artifacts peculiar to cadaveric images showed effective morphological and statistical improvement. Conclusions: Retrospective denoising of embalmed PMCT images showed significant morphological and statistical improvements in noise reduction and is feasible for current anatomy education and research.